Additions of Carbohydrate-Derived Alkoxyallenes to Imines and Subsequent Reactions to Enantiopure 2,5-Dihydropyrrole Derivatives - Hausherr, Arndt; Zimmer, Reinhold; Reissig, Hans-Ulrich (Synthesis, 2019)
The additions of six alkoxyallenes bearing carbohydrate-derived chiral auxiliaries to imines were systematically studied. The reactions of three lithiated 1-alkoxypropa-1,2-dienes with an N-tosyl imine revealed that the diacetone fructose-derived auxiliary provided the highest diastereoselectivity of 91:9. The preferred absolute configuration of the newly formed stereogenic center was determined by subsequent ozonolysis of the allene moiety, transesterification and comparison with literature data. The analogous reactions of three axially chiral 3-nonyl-substituted 1-alkoxyallenes with these auxiliaries confirm these results and also prove that the configuration of the generated stereogenic center was only steered by the auxiliaries, whereas the chiral axis has essentially no influence. In general, four diastereomers were obtained in various portions, depending on the ratio of the two precursor allene diastereomers and on the auxiliary employed. The obtained diastereomeric allenyl amines were cyclized under different conditions. As expected, under basic conditions, a stereospecific cyclization occurred, whereas under silver nitrate catalysis partial isomerization at the allene stage was observed. Under both conditions the 2,5-cis-disubstituted dihydropyrroles were formed faster than the trans-isomers. Several of the 2-substituted or 2,5-disubstituted dihydropyrrole derivatives could be isolated in diastereomerically pure form and were subsequently converted into the expected pyrrolidin-3-ones by removal of the carbohydrate-derived auxiliary under acidic conditions. The desired products were obtained in good yield and with high enantiopurity. They are suitable starting materials for the synthesis of enantiopure pyrrolidine natural products.
Keywords: alkoxyallenes; axial chirality; carbohydrate derivatives; imines; lithiation; nitrogen heterocycles; pyrrolidines